The Effectiveness of Rosetta Stone App on EFL Learners Listening Comprehension on the Student of Sman 5 Cirebon - Vica Via Vanesa (MATCHA: Journal of Modern Approaches to Communication, Humanities, and Academia, 2025)
This study investigates the impact of the Rosetta Stone application on enhancing listening comprehension among eleventh-grade students at SMAN 5 Cirebon, Indonesia. English proficiency is essential in Indonesia, yet many students struggle, particularly with listening skills. The research employed a quasi-experimental design, featuring pre-tests and post-tests to assess the effectiveness of the Rosetta Stone app compared to traditional teaching methods. The results indicated a significant improvement in the experimental group, which used Rosetta Stone, with average post-test scores increasing from 63.00 to 81.00. In contrast, the control group, which received conventional instruction, improved from 60.00 to 73.00. This demonstrates that the app effectively enhances students’ listening comprehension abilities. Additionally, a questionnaire revealed that student motivation to use the Rosetta Stone app was primarily driven by its engaging features and interactive video content. A majority of students expressed that these aspects significantly contributed to their learning experience. The findings suggest that integrating technology, such as the Rosetta Stone application, can lead to improved English listening skills, offering a more dynamic and effective approach to language learning. This study highlights the potential of innovative teaching methods and technological tools in fostering better language acquisition, providing valuable insights for educators aiming to enhance English proficiency in students. Overall, the Rosetta Stone app proves to be a beneficial resource in addressing the challenges of English language learning, particularly in listening comprehension.